BBD Driven Fabrication of Hydroxyapatite Engineered Risedronate Loaded Thiolated Chitosan Nanoparticles and Their In Silico, In Vitro, and Ex Vivo Studies - Zoya Saifi; Tanya Ralli; Md. Rizwanullah; Meraj Alam; Divya Vohora; Showkat R. Mir; Saima Amin; Sadia Ameen (Micromachines, 2023)
Risedronate sodium (RIS) exhibits limited bioavailability and undesirable gastrointestinal effects when administered orally, necessitating the development of an alternative formulation. In this study, mPEG-coated nanoparticles loaded with RIS-HA-TCS were created for osteoporosis treatment. Thiolated chitosan (TCS) was synthesized using chitosan and characterized using DSC and FTIR, with thiol immobilization assessed using Ellman’s reagent. RIS-HA nanoparticles were fabricated and conjugated with synthesized TCS. Fifteen batches of RIS-HA-TCS nanoparticles were designed using the Box–Behnken design process. The nanoparticles were formulated through the ionic gelation procedure, employing tripolyphosphate (TPP) as a crosslinking agent. In silico activity comparison of RIS and RIS-HA-TCS for farnesyl pyrophosphate synthetase enzyme demonstrated a higher binding affinity for RIS. The RIS-HA-TCS nanoparticles exhibited 85.4 ± 2.21% drug entrapment efficiency, a particle size of 252.1 ± 2.44 nm, and a polydispersity index of 0.2 ± 0.01. Further conjugation with mPEG resulted in a particle size of 264.9 ± 1.91 nm, a PDI of 0.120 ± 0.01, and an encapsulation efficiency of 91.1 ± 1.17%. TEM confirmed the spherical particle size of RIS-HA-TCS and RIS-HA-TCS-mPEG. In vitro release studies demonstrated significantly higher release for RIS-HS-TCS-mPEG (95.13 ± 4.64%) compared to RIS-HA-TCS (91.74 ± 5.13%), RIS suspension (56.12 ± 5.19%), and a marketed formulation (74.69 ± 3.98%). Ex vivo gut permeation studies revealed an apparent permeability of 0.5858 × 10−1 cm/min for RIS-HA-TCS-mPEG, surpassing RIS-HA-TCS (0.4011 × 10−4 cm/min), RIS suspension (0.2005 × 10−4 cm/min), and a marketed preparation (0.3401 × 10−4 cm/min).